Spectroscopic Assessment of Normal Cortical Bone: Differences in Relation to Bone Site and Sex - Nikolaos Kourkoumelis; Margaret Tzaphlidou (The Scientific World Journal)
Bone is a highly complex, composite tissue and its properties normally vary with age, type, and disorders. Fourier transform infrared spectroscopy and energy-dispersive X-ray spectroscopy techniques were used to study the effect of bone sites and sex to mineral and matrix content and composition. The results show that in rats, all inorganic phases consist of poorly crystalline B-type carbonated apatite, while overall mineralization and carbonate content is virtually unaffected among samples. Statistically significant differences were detected for the nonapatitic environments of acid phosphate and carbonate content. The mean values for the Ca/P ratio point to an increasing trend from tibia to forearm, and to femoral sections.